Development of a new model-based integrated process design and control for heat exchanger networks - Abd. Hamid, Mohd. Kamaruddin (2012)
This paper presents the development of a new model-based integrated process design and control (IPDC) methodology for heat exchanger networks (HENs). Many methods for HENs synthesis have been developed over the past decades, which aim to provide HENs designs that yield a reasonable trade-off between capital and operating costs. However, in most of HENs synthesis activities, the sole consideration in solution derivation is about design cost. Process operational issue especially controllability is frequently not a concern in the process design. As a result, the controllability of a designed HEN may be questionable. Industrial practice has made it clear that process controllability should be considered during process synthesis. The HENs design can be further improved to ensure that the design is more cost efficient and controllable. This can be achieved by developing a new model-based IPDC methodology, which includes cost optimality and controllability aspects at the early HEN design stage. Here, the IPDC problem for HENs which is typically formulated as a mathematical programming (optimization with constraints) problem is solved by decomposing it into four sequential hierarchical stages: (i) target selection, (ii) HEN design analysis, (iii) controllability analysis, and (iv) optimal selection and verification. In Stage 1, the minimum utility target for both external heat and cold utilities of the whole process plant is selected at the pinch point by using stream temperature versus enthalpy plot (STEP) concept. The capability of the proposed methodology was tested using biomethanol plant.